2009
DOI: 10.1128/ec.00165-09
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Responses of Candida albicans to Epithelial and Endothelial Cells

Abstract: Candida albicans interacts with oral epithelial cells during oropharyngeal candidiasis and with vascular endothelial cells when it disseminates hematogenously. We set out to identify C. albicans genes that govern interactions with these host cells in vitro. The transcriptional response of C. albicans to the FaDu oral epithelial cell line and primary endothelial cells was determined by microarray analysis. Contact with epithelial cells caused a decrease in transcript levels of genes related to protein synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 77 publications
(114 reference statements)
4
70
2
Order By: Relevance
“…The list of genes that were found to be differentially expressed does not overlap significantly with either of these previous studies. For example, of the 127 genes that were differentially expressed during at least one time point in one cell type in the current study, five were reported by Park et al (2009) and 11 were reported by Wachtler et al (2011) to have changed in the same direction. There are several possible explanations for the poor concordance.…”
Section: Wwwgenomeorgmentioning
confidence: 53%
See 3 more Smart Citations
“…The list of genes that were found to be differentially expressed does not overlap significantly with either of these previous studies. For example, of the 127 genes that were differentially expressed during at least one time point in one cell type in the current study, five were reported by Park et al (2009) and 11 were reported by Wachtler et al (2011) to have changed in the same direction. There are several possible explanations for the poor concordance.…”
Section: Wwwgenomeorgmentioning
confidence: 53%
“…Cold Spring Harbor Laboratory Press on April 27, 2019 -Published by genome.cshlp.org Downloaded from To our knowledge, only two other studies, both microarraybased, examined the response of epithelial cells or endothelial cells to C. albicans using a similar time-matched negative control sample that consisted of fungal cells incubated in tissue culture media without host cells (Park et al 2009;Wachtler et al 2011). The list of genes that were found to be differentially expressed does not overlap significantly with either of these previous studies.…”
Section: Wwwgenomeorgmentioning
confidence: 99%
See 2 more Smart Citations
“…This allowed for the construction of a large set of mutants, though it was still not as efficient as it would be for a haploid strain. This library is widely used by the Candida community Norice et al, 2007;Park et al, 2009). Spreghini et al (2003) exploited transposon mutagenesis to add an epitope to the putative cell wall protein, Dfg5p.…”
Section: Transposon-mediated Insertional Mutagenesismentioning
confidence: 99%